The existence of positive solution of systems of Volterra nonlinear difference equations - Zhu, Jiang; Liu, X. (Нелінійні коливання, 2006)
In this paper, a classification scheme for the eventually positive solutions of a class of two-dimensional Volterra nonlinear difference equations is given in terms of asymptotic magnitudes. Some necessary as well as sufficient conditions for the existence of such solutions are provided, without any monotonicity conditions on the nonlinear term. Для згодом додатних розв’язкiв деякого класу двовимiрних вольтеррiвських нелiнiйних рiвнянь наведено класифiкацiйну схему в термiнах умов на асимптотику. Наведено також деякi необхiднi i достатнi умови iснування таких розв’язкiв без вимоги монотонностi нелiнiйного члена.